2012
DOI: 10.1038/bjc.2012.336
|View full text |Cite
|
Sign up to set email alerts
|

Systematic lymphadenectomy in ovarian cancer at second-look surgery: a randomised clinical trial

Abstract: Background:The role of systematic aortic and pelvic lymphadenectomy (SAPL) at second-look surgery in early stage or optimally debulked advanced ovarian cancer is unclear and never addressed by randomised studies.Methods:From January 1991 through May 2001, 308 patients with the International Federation of Gynaecology and Obstetrics stage IA–IV epithelial ovarian carcinoma were randomly assigned to undergo SAPL (n=158) or resection of bulky nodes only (n=150). Primary end point was overall survival (OS).Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…In this patient group, the systemic pelvic and paraaortic lymphadenectomy were not associated with a better OS or progression-free survival (PFS). Similar results were observed in patients with ovarian cancer at early stages (38) and those who underwent lymphadenectomy after primary surgery (39). Due to the limited data on lymph nodes removal such as number, location, postoperative complication, and recurrence rate, we could not get further results.…”
Section: Discussionmentioning
confidence: 54%
“…In this patient group, the systemic pelvic and paraaortic lymphadenectomy were not associated with a better OS or progression-free survival (PFS). Similar results were observed in patients with ovarian cancer at early stages (38) and those who underwent lymphadenectomy after primary surgery (39). Due to the limited data on lymph nodes removal such as number, location, postoperative complication, and recurrence rate, we could not get further results.…”
Section: Discussionmentioning
confidence: 54%
“…A meta-analysis indicated that lymphadenectomy can improve the survival of patients with advanced-stage epithelial ovarian cancer (EOC) [ 8 ]. However, the role of lymphadenectomy in EOC is still controversial [ 9 - 11 ]. The lymph node status of EOC patients is currently determined by the number of positive lymph nodes (PLNs), and this is affected by the number of resected lymph nodes (RLNs), and therefore may cause stage migration in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…These articles, including 1783 cases and 1705 controls, were published between 1994 and 2013 and consisted of 11 observational studies (16)(17)(18)(19)(20)(23)(24)(25)(27)(28)(29) and three RCTs (21)(22)26). Among the included studies, SL was defined as follows: (i) either pelvic or paraaortic lymphadenectomy or both (16)(17)(19)(20)21,(23)(24)(25)(26)(27)(28)(29); (ii) >20 resected pelvic and para-aortic lymph nodes (18,22).…”
Section: Study Characteristicsmentioning
confidence: 99%